2015
DOI: 10.1513/annalsats.201406-271oc
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Weight Loss and Physical Activity Intervention in Obese Adults with Asthma. A Randomized Trial

Abstract: Moderately and severely obese adults with uncontrolled asthma can safely participate in evidence-based lifestyle intervention for weight loss and active living. The modest average weight and activity improvements are comparable to those shown to reduce cardiometabolic risk factors in studies of similar interventions in other populations but are not associated with significant net benefits for asthma control or other clinical asthma outcomes in the current population. Instead, weight loss of 10% or greater may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
104
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 107 publications
(120 citation statements)
references
References 39 publications
0
104
1
3
Order By: Relevance
“…As we have done in our previous RCTs [23][24][25][26], we implemented the following strategies to maximize retention: (1) careful staff selection and standardized training in rapport building, MI techniques, trialspecific protocols and problem solving techniques as applicable to their study roles; (2) legally sufficient and effective informed consent; (3) cautious eligibility screening, including assessment of willingness and motivation to adhere to data collection and treatment requirements; (4) edification of participants about the importance of follow-up assessments regardless of treatment adherence; (5) prudent participant incentives and flexible scheduling; (6) promotion of study identity; (7) ongoing monitoring of recruitment and retention; (8) up-todate contact information for the participant and two emergency contacts; (9) diligent efforts to re-engage inactive participants; and (10) prioritization of outcome measures when not all measures may be collected from a participant [19,20].…”
Section: Retentionmentioning
confidence: 81%
“…As we have done in our previous RCTs [23][24][25][26], we implemented the following strategies to maximize retention: (1) careful staff selection and standardized training in rapport building, MI techniques, trialspecific protocols and problem solving techniques as applicable to their study roles; (2) legally sufficient and effective informed consent; (3) cautious eligibility screening, including assessment of willingness and motivation to adhere to data collection and treatment requirements; (4) edification of participants about the importance of follow-up assessments regardless of treatment adherence; (5) prudent participant incentives and flexible scheduling; (6) promotion of study identity; (7) ongoing monitoring of recruitment and retention; (8) up-todate contact information for the participant and two emergency contacts; (9) diligent efforts to re-engage inactive participants; and (10) prioritization of outcome measures when not all measures may be collected from a participant [19,20].…”
Section: Retentionmentioning
confidence: 81%
“…Improvements were seen in asthma symptoms, quality of life, peak flow, and markers of oxidative stress and inflammation. 64 More recent studies published by Pakhale et al, 65 Scott et al, 66 and Ma et al 68 implementing weight loss in the form of liquid diet (Pakhale), or diet and exercise (Scott and Ma), suggest improved asthma outcomes in patients who lose a significant amount of weight. There appears to be a threshold for improving asthma symptoms, with a 5%-10% loss of body weight required to significantly improve asthma control.…”
Section: Evidence That Weight Loss Improves Asthma Controlmentioning
confidence: 99%
“…62 A summary of these studies is described in Table 3. [63][64][65][66][67][68][69] Although the quality and sample size of these studies vary, the majority of these studies have found improvements in asthma-related quality of life, lung function, and symptom scores with significant weight loss. 62,63 Weight loss studies have included surgery, low calorie diets, exercise, and combined diet-exercise interventions.…”
Section: Evidence That Weight Loss Improves Asthma Controlmentioning
confidence: 99%
“…Evidence shows that obesity may influence the efficacy of asthma treatments, and weight loss may enhance the efficacy of the treatment. The data from a recent study showed that the anthropometric obesity measures correlated with a poor efficacy and poor quality of life and life in obese patients with asthma 34,35 , and increased the risk of hospitalizations 36 .…”
Section: Obesity and Asthma Managementmentioning
confidence: 99%